Relative Yield, Profit and Water Productivity of Crops in IGNP Stage-I - Rathore, V S; Yadava, N D; Nangia, V; Kumar, R; Birbal, Birbal; Soni, M L; Kumawat, Amit (Annals of Arid Zone, 2017)
The choice of an appropriate crop and cropping systems is essential for achieving higher yield, profit and resource use efficiencies. Yield, returns and water productivity are important factors for determining suitability of crops and cropping systems in hot arid environment. A two-year (2012-13 and 2013-14) study was conducted in IGNP stage-I command area to determine productivity, profitability and water productivity of different crops and cropping systems. Yield, profit and water productivity varied markedly among different crops and cropping systems. The economic yield of crops varied from 1.6 Mg ha-1 to 4.2 Mg haha-1; and biomass yield varied from 5.8 Mg haha-1 to 10.1 Mg haha-1. The net return varied from Rs. 31421 haha-1 to Rs. 213680 haha-1. The clusterbean had highest profit followed by cotton, wheat, barley and Indian mustard. Clusterbean and wheat was the most profitable crop of kharif and rabi season, respectively. Among the kharif season crops, the clusterbean was 1.4-times more water productive than cotton, and among rabi season crops, barley was 1.3- and 1.6-times more water productive than wheat and Indian mustard, respectively. Cotton–wheat cropping sytem had highest yield followed by cotton-barley, clusterbean-wheat, cotton-mustard, and clusterbean-mustard systems. The clusterbean based cropping systems were more profitable and water use efficiecnt than cotton based cropping systems.